Quantitative Assessment of Optimal Bone Marrow Site for the Isolation of Porcine Mesenchymal Stem Cells - J. S. McDaniel; B. Antebi; M. Pilia; B. J. Hurtgen; S. Belenkiy; C. Necsoiu; L. C. Cancio; C. R. Rathbone; A. I. Batchinsky (Stem Cells International)
Background. One of the most plentiful sources for MSCs is the bone marrow; however, it is unknown whether MSC yield differs among different bone marrow sites. In this study, we quantified cellular yield and evaluated resident MSC population from five bone marrow sites in the porcine model. In addition, we assessed the feasibility of a commercially available platelet concentrator (Magellan® MAR01™ Arteriocyte Medical Systems, Hopkinton, MA) as a bedside stem cell concentration device. Methods. Analyses of bone marrow aspirate (BMA) and concentrated bone marrow aspirate (cBMA) included bone marrow volume, platelet and nucleated cell yield, colony-forming unit fibroblast (CFU-F) number, flow cytometry, and assessment of differentiation potential. Results. Following processing, the concentration of platelets and nucleated cells significantly increased but was not significantly different between sites. The iliac crest had significantly less bone marrow volume; however, it yielded significantly more CFUs compared to the other bone marrow sites. Culture-expanded cells from all tested sites expressed high levels of MSC surface markers and demonstrated adipogenic and osteogenic differentiation potential. Conclusions. All anatomical bone marrow sites contained MSCs, but the iliac crest was the most abundant source of MSCs. Additionally, the Magellan can function effectively as a bedside stem cell concentrator.